The user’s perspective: Rethinking the concept of work in the context of the Norwegian welfare state (Journal of Comparative Social Work, 2025)
This article deals with issues of work inclusion, with a particular focus on the user’s perspective on work, and the work inclusion policy in Norway. An expanded concept of work is applied, which includes all human activities that contribute social value to society, and not only paid work. However, work is typically seen as activities that are valued in society. One consequence of this is that some activities are hidden and devalued as work, although they contribute socially valuable means. This is the case for a range of activities performed by clients in the welfare state who contribute to fulfilling the objectives of welfare policy. The article argues that the user’s perspective is important to understand how work inclusion comprises several activities that can be seen as work. Based on data from 14 in-depth interviews with young adults currently outside the labour market due to health problems, the study elucidates how being ill and part of work inclusion programmes are not a passive existence, but rather demanding work. The overarching question addresses how the young adults perceive their situation. They wanted to enter working life, in line with hegemonic norms, but health challenges meant that they did not always succeed. Mental and physical health problems affected their everyday lives in many ways. Pain, anxiety and fatigue made their days variable and unpredictable, and limited their level of activity and pace, both in daily chores and due to work inclusion. The article discusses some implications for policy-making, as well as for social work in the front line of the welfare state. Key factors involve the need for time, understanding and counselling to establish tasks and a workload that are sustainable over time.